Zyras (Diaulaconia) artemis sp. n., a new termitophilous species from Taiwan (Coleoptera: Staphylinidae: Aleocharinae: Lomechusini) - Liang, Wei-Ren; Maruyama, Munetoshi; Li, Hou-Feng (Zootaxa, 2017)
The staphylinid tribe Lomechusini is known for the diverse associations with ants or termites. A new species of rove beetle belonging to Zyras (Diaulaconia) is found to be associated with the fungus-growing termite, Odontotermes formosanus (Shiraki, 1909), and is showing meticulous predatory behavior. In the present study, this species is described as Zyras (Diaulaconia) artemis Liang, Maruyama & Li, sp. n. Its assignment to the subgenus Diaulaconia is based on the comparison of female spermatheca, male aedeagus, and male secondary characters. The habitus photographs and the line drawings of diagnostic characters and their variations are provided. The current knowledge about the taxonomy, phylogeny, and ecology of Diaulaconia is discussed. The checklist of Diaulaconia species of Taiwan is updated.